Color-tunable single-fluorophore supramolecular system with assembly-encoded emission - Qian Wang (Nature Portfolio, 2020)
Regulating fluorescent properties of small molecules in a controlled manner has been a fundamental research goal but realizing multi-color emission from a single fluorophore remains challenging. Here the authros demonstrate that combined pyrene fluorophore and acylhydrazone units show multi-color switchable fluorescent at different assembled states.